2016
DOI: 10.1371/journal.pone.0153439
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Livestock in Big Cat Prey Choice Using Spatiotemporal Availability Patterns

Abstract: Livestock is represented in big cat diets throughout the world. Husbandry approaches aim to reduce depredation, which may influence patterns of prey choice, but whether felids have a preference for livestock or not often remains unclear as most studies ignore livestock availability. We assessed prey choice of the endangered Persian leopard (Panthera pardus saxicolor) in Golestan National Park, Iran, where conflict over livestock depredation occurs. We analyzed leopard diet (77 scats) and assessed wild and dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…In the Maasai Mara, cheetahs do occasionally predate on livestock (Broekhuis, Thuo, & Hayward 2018) and as livestock numbers outside the wildlife areas are high (Broekhuis, Cushman, & Elliot, 2017b; Ogutu et al., 2016) it is potentially an easy food source for cheetahs. However, it has been shown that some carnivores, including cheetahs, prefer wild prey over domestic (Ghoddousi et al., 2016; Marker, 2002) and as wild prey species outside the wildlife areas are declining (Ogutu et al., 2016) it is possible that cheetahs prefer the wildlife areas where large numbers of wild prey are still readily available.…”
Section: Discussionmentioning
confidence: 99%
“…In the Maasai Mara, cheetahs do occasionally predate on livestock (Broekhuis, Thuo, & Hayward 2018) and as livestock numbers outside the wildlife areas are high (Broekhuis, Cushman, & Elliot, 2017b; Ogutu et al., 2016) it is potentially an easy food source for cheetahs. However, it has been shown that some carnivores, including cheetahs, prefer wild prey over domestic (Ghoddousi et al., 2016; Marker, 2002) and as wild prey species outside the wildlife areas are declining (Ogutu et al., 2016) it is possible that cheetahs prefer the wildlife areas where large numbers of wild prey are still readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Selective killing of livestock by carnivores has high practical importance as it may identify most vulnerable livestock species or intraspecific categories and potentially help reduce conflicts by targeting these high‐risk species or categories. Carnivores may give preference to particular livestock species and take proportionally higher numbers than available (Chetri, Odden, & Wegge, ; Elbroch & Wittmer, ) or, alternatively, avoid or prey them opportunistically (Ghoddousi et al., ; Lyngdoh et al., ; Suryawanshi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As the number of scat samples with remains of the i ‐th prey ( n i ) was not always reported in literature sources, we calculated it from available data on the frequency of prey occurrence in scats ( f i ) and the total number of collected scats ( n total ) using the relationship f i = ( n i / n total ) × 100 (Ghoddousi et al. ). As Wachter et al.…”
Section: Methodsmentioning
confidence: 99%
“…, Ghoddousi et al. ). Depredation often leads to retaliatory killing of large carnivores by humans, especially of big cats such as the lion Panthera leo , tiger Panthera tigris , jaguar Panthera onca , leopard Panthera pardus , snow leopard Panthera uncia , puma Puma concolor, and cheetah Acinonyx jubatus , which prey on economically valuable livestock and occasionally may attack humans (Inskip & Zimmermann , Loveridge et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation